The American Psychiatric Association - Riba, Michelle B. (Int Psychiatry, 2005)
The American Psychiatric Association (APA) is a medical specialty society that represents nearly 36 000 psychiatrists from the United States and Canada, as well as around the globe. It is the longest serving medical specialty society. As a leader in the mental health field, the APA continually supports the diagnosis and treatment of patients with mental illnesses, including substance use disorders, and also supports prevention and research. The APA acts as an advocate for psychiatrists and their patients.